A Collective Exploration : Unveiling Elephant Memory Capacities Through Community Experience - Koo Huang, Qing Yuan; Mohamad Abdullah, Nazirah; Lok, Huey Kei; Phoo, Qiao Lin; Khairunizan, Huda Khalidah; Bakri, Nur A'alia Atierah (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the memory capabilities of elephants through a collective exploration framework, emphasizing community observations and ecological implications. This research was conducted in Kampung Lukut by using qualitative methods, that are interviewing with 20 villagers, and an ethogram-based observations of an elephant named Nina in Johor Elephant Sanctuary. This study aimed to: (i) analyse the adaptive significance of memory in elephant social dynamics and survival strategies through communities, (ii) identify the social interactions that shows the effect of elephant memory within their communities, and (iii) uncover multifaced aspects of elephant memory, including social, spatial, and cognitive dimensions. Finding highlighted elephant’s locomotion, social structures, and interactions with humans. Behavioural responses to stimuli, such as bee sounds, were recorded, together with the community interview, insights into special memory and emotional intelligence. The study identifies the adaptive significance of memory in survival strategies and gives recommendations for enhancing conservation efforts.